Quantification of 4-hydroxy-2-nonenal-protein adducts in the in vivo gastric digesta of mini-pigs using a GC-MS/MS method with accuracy profile validation. Issue 8 (15th July 2016) - Delosière, Mylène; Santé-Lhoutellier, Véronique; Chantelauze, Céline; Durand, Denys; Thomas, Agnès; Joly, Charlotte; Pujos-Guillot, Estelle; Rémond, Didier; Comte, Blandine; Gladine, Cécile; Guy, Alexandre; Durand, Thierry; et al.
Abstract : Quantification of 4-hydroxy-2-nonenal-protein adducts in the in vivo gastric digesta of mini-pigs using a validated GC-MS/MS method. Abstract : Hydroxyalkenals are lipid oxidation end-products resulting from the oxidation of polyunsaturated fatty acids (PUFA). This study aimed at quantifying the production of 4-hydroxy-2-nonenal-protein adducts (HNE-P) via Michael addition from n-6 PUFA oxidation in the gastric digesta of mini-pigs after the consumption of meat-based meals with different plant antioxidant contents. Using the accuracy profile procedure, we validated an extraction protocol for the quantification of HNE-P by GC-MS/MS in gastric contents. The formation of HNE-P in the gastric compartment was observed for the first time, with concentrations ranging from less than 0.52 to 1.33 nmol HNE-P per 500 mg digesta. Nevertheless, most gastric HNE-P levels were below the limit of quantification of 0.52 nmol HNE-P per 500 mg digesta. In this animal study, the protective effect of plant antioxidant sources on HNE-P formation was not evidenced contrasting with the results using TBARS as markers.